Christian Apologetics as Cross-Cultural Dialogue - van den Toren, Benno (Continuum, 2011)
Christian apologetics is in crisis. Old concepts do no longer hold andpost-modern development pose new questions. Benno van den Toren arguesfor an apologetic witness that is an exercise in cross-culturaldialogue aimed at persuading our conversation partners of the relevanceof a life centred on the reality revealed in Jesus Christ. Somesignificant steps have been made toward the development of such a newapologetic practice. The aim of this book is to provide theological andphilosophical basis for a new paradigm for Christian apologeticdialogue with our post-modern and multi-cultural world and t